Attidues of graduate students toward distance education, educational technologies and independent learning - (:unkn) unknown (My University, 2007)
Distance education systems are being used in along with the traditional education systems in order to respond to the demand for higher education. Technological advancements, interactive learning possibilities are forcing the traditional universities to make more use of the distance education systems and technologies. Most of the traditional universities to create the opportunity for their students to be independent learners and learners who can organize their learning processes by using distance education systems and technologies. It is thought that students who can learn on their own and who can organize their learning processes will be more likely to use lifelong learning opportunities. In Turkey where there is a great demand for higher education, the use of distance education systems and technologies in traditional universities is not common. These traditional universities can make use of the distance education systems and technologies in certain lectures and cope with the pressure of the increasing number of students. Successful implementation of the distance education applications in traditional universities will affect the mega Turkish education system in a positive way. In this study, the views of the doctoral students at traditional universities on the use of distance education systems and technologies and independent learning are determined. Findings indicate that doctoral students do not have a positive attitude towards the use of distance education systems and technologies, and they do not agree with the idea that distance education systems can support independent learning.
Keywords: Distance education; Educational technologies; Independent learning